Naturalization Policies, Education and Citizenship Multicultural and Multi-Nation Societies in International Perspective - Kiwan, D.; Kiwan, D. (Palgrave Politics of Identity and Citizenship Series, 2013)
This book examines constructions of 'national' citizenship in the context of perceived internal division, including devolution, multiculturalism, ethno-religious conflict, post-conflict and refugees, drawing on a wide range of countries such as Belgium, Denmark, France, Germany, the UK, Ukraine, Canada and Palestinians in Lebanon.